Healthcare utilization associated with antimicrobial resistance at a tertiary hospital in Vietnam: A retrospective observational study from 2016 to 2021 - Nga Thi-Quynh Nguyen; Nhien Phan-Thuy Nguyen; Quynh Thuy Truong; Thao Phuong Huynh; Hong-Nguyen Tran-Thi; Minh Van Hoang; Hai-Yen Nguyen-Thi (PLoS ONE, 2025)
Background Despite the increasing burden of antimicrobial resistance (AMR), specifically on priority ESKAPE pathogens, studies examining the economic impact of AMR in low- and lower-middle-income countries have been scarce and require further investigation to optimize the post-COVID resource allocation. Objectives To quantify the incremental hospital costs and length of stay (LOS) associated with antimicrobial-resistant versus -susceptible among priority ESKAPE pathogens from the healthcare sector perspective. Methods We conducted a retrospective observational study of patients hospitalized at the Hospital for Tropical Diseases from 2016−2021 with non-duplicate isolates of any ESKAPE pathogens from clinical specimens. The patients were then stratified into resistant- and susceptible- groups by the WHO classification. Multivariate generalized linear regression and negative binomial regression with linear spline at COVID-19 occurrence were employed to evaluate the incremental hospital costs and LOS due to AMR, respectively. These regressions were adjusted for sociodemographic and clinical characteristics. We applied difference-in-difference (DiD) to estimate the differential cost between resistant and susceptible groups regarding COVID-19 change. Results During the six-year period, 4,197 out of 6,670 patients (62.92%) were isolated with priority pathogens, with the highest prevalence of priority pathogens observed in 3GCREC and MRSA (accounting for 45.63% and 25.33%, respectively). After covariate adjustments, the incremental hospital costs per resistant patient were significantly higher across most pathogens except for patients tested with MRSA results (average CRAB $3,980; CRPA $1,000; 3GCREC $444; 3GCRKP $1,942; MRSA -$326), while incremental LOS ranged from 1.40 days for 3GCREC (95%CI: 0.69–2.10 ) to 12.54 days for CRPA (95%CI: 11.12–13.97). COVID-19 significantly enlarged the hospital cost gaps between patients with antibiotic-resistant and antibiotic-susceptible profiles, with A.baumannii (CRAB vs. CSAB) showing the highest DiD at $9,116 (95%CI: $6,019-$12,213). Conclusion The incremental hospital costs of AMR were significant, with the highest one observed in CRAB patients, and the difference between resistant and susceptible cases widened during the COVID-19 pandemic.